2020
DOI: 10.3390/cells9010187
|View full text |Cite
|
Sign up to set email alerts
|

The Ebola Virus Nucleoprotein Recruits the Nuclear RNA Export Factor NXF1 into Inclusion Bodies to Facilitate Viral Protein Expression

Abstract: Ebola virus (EBOV) causes severe outbreaks of viral hemorrhagic fever in humans. While virus-host interactions are promising targets for antivirals, there is only limited knowledge regarding the interactions of EBOV with cellular host factors. Recently, we performed a genome-wide siRNA screen that identified the nuclear RNA export factor 1 (NXF1) as an important host factor for the EBOV life cycle. NXF1 is a major component of the nuclear mRNA export pathway that is usurped by many viruses whose life cycles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…The phosphorylated mitogen-activated protein kinase p38, a key regulator of cellular inflammatory and stress responses, and the O-linked N -acetylglucosamine (OGN) transferase, an enzyme that catalyzes the posttranslational addition of OGN to protein and is also involved in stress response, are sequestered in RSV IBs [ 99 ]. Finally, EBOV NP recruits several proteins into the IBs, which include the nuclear RNA export factor NFX1 to drive viral protein synthesis [ 100 ] and the histone-lysine-methyltransferase SMYD3 [ 101 ] as well as the CAD protein [ 102 ] to facilitate mRNA transcription and replication.…”
Section: Interaction Of Viral Liquid Ibs With Host-cell Machineriesmentioning
confidence: 99%
“…The phosphorylated mitogen-activated protein kinase p38, a key regulator of cellular inflammatory and stress responses, and the O-linked N -acetylglucosamine (OGN) transferase, an enzyme that catalyzes the posttranslational addition of OGN to protein and is also involved in stress response, are sequestered in RSV IBs [ 99 ]. Finally, EBOV NP recruits several proteins into the IBs, which include the nuclear RNA export factor NFX1 to drive viral protein synthesis [ 100 ] and the histone-lysine-methyltransferase SMYD3 [ 101 ] as well as the CAD protein [ 102 ] to facilitate mRNA transcription and replication.…”
Section: Interaction Of Viral Liquid Ibs With Host-cell Machineriesmentioning
confidence: 99%
“…Consequently, the NXF1 promotes the export of viral mRNA:NXF1 complexes from inclusion bodies. This provides a basis for new therapeutic approaches for viruses[ 84 ]. The ribosomal proteins (RPs) contain 60S subunit control translation of specific mRNAs.…”
Section: The Role Of Lipidome During the Host-viral Interactionsmentioning
confidence: 99%
“…CoIPs were performed as previously described [19]. Briefly, 293T cells were seeded in 6-well plates and transfected with expression plasmids encoding FLAG/HA-tagged CAD and EBOV-NP using Transit LT-1 (Mirus Bio LLC) following the manufacturer's instructions.…”
Section: Co-immunoprecipitation Of Viral Proteinsmentioning
confidence: 99%
“…Furthermore, several cellular kinases and phosphatases are known to localize in inclusion bodies to support EBOV replication and transcription [16][17][18]. Finally, we previously showed that EBOV NP recruits the nuclear RNA export factor 1 (NXF1) into inclusion bodies to facilitate viral mRNA export from these structures into the cytoplasm [19]. Despite this recent progress in our understanding of the interplay between host factors and EBOV, there remains a considerable need to identify and, more importantly, characterize further host factors required for EBOV replication to identify novel targets for antiviral drug development.…”
Section: Introductionmentioning
confidence: 99%